The Nearctic Ecclisomyia species (Trichoptera: Limnephilidae) - Givens, Donald R. (Zootaxa, 2018)
The Nearctic species of Ecclisomyia are reviewed with new descriptions of the pupae of the four recognized species. The larvae of E. bilera Denning 1951, E. maculosa Banks 1907, and E. simulata Banks 1920 are described. A supplementary description is provided for the larva of E. conspersa Banks 1907. Genetic and morphological information is provided to support the recent restoration of E. simulata as a valid species. Keys to the males, females, pupae, and larvae are provided. Biological and distributional data are also included.